2022
DOI: 10.1002/jcsm.13010
|View full text |Cite
|
Sign up to set email alerts
|

Ambra1 deficiency impairs mitophagy in skeletal muscle

Abstract: Background Maintaining healthy mitochondria is mandatory for muscle viability and function. An essential surveillance mechanism targeting defective and harmful mitochondria to degradation is the selective form of autophagy called mitophagy. Ambra1 is a multifaceted protein with well-known autophagic and mitophagic functions. However, the study of its role in adult tissues has been extremely limited due to the embryonic lethality caused by full-body Ambra1 deficiency. Methods To establish the role of Ambra1 as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…It causes an imbalance in muscle mass maintenance and induces muscle loss [34]. An essential surveillance mechanism targeting defective and harmful mitochondria to degradation is the selective form of autophagy called mitophagy [35]. Impaired mitophagy is a primary pathogenic event underlying diverse aging-associated diseases such as sarcopenia [36].…”
Section: Discussionmentioning
confidence: 99%
“…It causes an imbalance in muscle mass maintenance and induces muscle loss [34]. An essential surveillance mechanism targeting defective and harmful mitochondria to degradation is the selective form of autophagy called mitophagy [35]. Impaired mitophagy is a primary pathogenic event underlying diverse aging-associated diseases such as sarcopenia [36].…”
Section: Discussionmentioning
confidence: 99%
“…Protein concentration was determined by the BCA Protein Assay Kit (Thermo Fisher Scientific), and 30–40 Îźg of each protein sample was subjected to SDS-PAGE in polyacrylamide Novex NuPAGE Bis-Tris 4–12% gels (Thermo Fisher Scientific), followed by electrotransfer onto polyvinylidene difluoride membranes (Millipore), as previously described ( Metti et al, 2020 ). Membranes were stained with Ponceau (Sigma-Aldrich) and blocked for 1 h with 5% non-fat dry milk (Bio-Rad, Hercules, CA, USA) in Tris-buffered saline solution containing 0.1% Tween 20 (TBS-T), and then incubated overnight at 4°C with the primary antibodies, as previously described ( Gambarotto et al, 2022 ). The following primary antibodies were used: mouse monoclonal anti-MyH3 (1:500; F1.652; Developmental Studies Hybridoma Bank, Iowa City, IA, USA), mouse monoclonal anti-MyoG (1:300; sc-12732; Santa Cruz Biotechnology, Dallas, TX, USA), rabbit polyclonal anti-phospho-GSK-3Îą/β (Ser 21/9) (1:1000; 9331S; Cell Signaling Technology, Danvers, MA, USA), rabbit monoclonal anti-β-catenin (1:500; ab32572; Abcam, Cambridge, UK), and mouse monoclonal anti-β-actin (1:3000; A5316; Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, these proteins facilitate the recruitment of LC3 or GABARAP proteins, thereby establishing connections between mitochondria and autophagosomes. For example, recent studies in skeletal muscle have shown that AMBRA1 (autophagy and beclin 1 regulator 1) relies on the E3 ubiquitin ligase HUWE1 (HECT, UBA, and WWE domain containing E3 ubiquitin protein ligase 1) to induce mitophagy, and specific knockout of AMBRA1 in mouse skeletal muscle can seriously impair skeletal muscle mass and mitophagy [ 103 , 104 ]. Consequently, it is imperative to expand our understanding of mitophagy beyond the PINK1–parkin pathway and consider the involvement of receptor-dependent pathway-related proteins.…”
Section: The Role Of Mitophagy In Skeletal Muscle Atrophymentioning
confidence: 99%